2019
DOI: 10.1016/j.heliyon.2019.e02632
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustainable agricultural production under farmer conditions in maize-gliricidia intercropping in Salima District, central Malawi

Abstract: Smallholder farmers in Malawi are faced with limited options for climate smart agriculture that would restore soil fertility and increase maize yield. Ten plots of maize intercropped with Gliricidia sepium (MIG) and 10 traditional sole-maize (TSM) plots (0.2 ha each) were studied under farmer conditions from 2013/14 to 2017/18 in Salima District, central Malawi. The aim was to assess performance of MIG on soil fertility restoration and maize yield in degraded agricultural land. G. sepium trimmings were incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is extensively cultivated throughout the world not only for its high production but also for its high nutrition value. Maize is an essential nourishment for about 75% of the country's population, and most of the farmers grow maize as an individual crop in their fields [ 1 ]. Maize is consumed in roasted and fried form and also used in poultry feed and used as fodder for livestock.…”
Section: Introductionmentioning
confidence: 99%
“…It is extensively cultivated throughout the world not only for its high production but also for its high nutrition value. Maize is an essential nourishment for about 75% of the country's population, and most of the farmers grow maize as an individual crop in their fields [ 1 ]. Maize is consumed in roasted and fried form and also used in poultry feed and used as fodder for livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia has a high potential biodiversity, which considerable as economic and ecological bene t to the nation, but historical studies have been demonstrated that the dramatic human in uences on their natural resources affect ecological base. In line with this, (Nyirenda, 2019) money studies conducted on the socio-economic and environmental importance of agroforestry practices in south Ethiopia. Some of the researchers conducted their study on related topic like Alelign et al,(2011) conducted their study on assessment of agroforestry practices in Zegie peninsula, north western Ethiopia and it focus on socio-economic factors affecting sustainable utilization of agroforestry practices.…”
Section: Introductionmentioning
confidence: 68%
“…It is widely grown all over the world, not only because of its large yield but also for its excellent nutritional content. Maize is an important source of nutrition for around 70% of the nation's people, and most farmers cultivate it as a stand-alone crop on their farms [1]. Traditional reproduction methods with long cycles and low productivity are used in the development of traditional crops, particularly vegetables.…”
Section: Introductionmentioning
confidence: 99%